Peningkatan Prospek Penjualan Pedagang Sayur Di Pasar Nyanggelan Melalui Pelatihan Marketing Online - Devianti, Amelia; Wardani, Kadek Devi Kalfika Anggria; Gorda, A.A.Ngr.Eddy Supriyadinata (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2022)
The Covid-19 pandemic has presented a number of challenges for vegetable traders at the Nyanggelan Market, Panjer Village. The existence of regional restrictions has led to a decrease in the number of buyers which has an impact on the decline in the level of sales of vegetable traders at the Nyanggelan Market. To help the vegetable traders of Nyanggelan Village survive in the midst of a crisis, community service activities are carried out by providing online marketing training. supervision or monitoring stage, and evaluation stage. The result of this service activity is the formation of a social media account (instagram) "Sayur Pasar Nyanggelan" which is used as a means of promotion as well as buying and selling by vegetable traders at Pasar Nyanggelan. The results of this service activity elicited positive reactions from traders. Sales prospects began to increase and vegetable traders had a new medium to promote their wares. In the future, it is hoped that the account will continue to grow and its use can be expanded.